Embodied Energy in Export Flows Along Global Value Chain: A Case Study of China’s Export Trade - Zhang, Boya; Bai, Shukuan; Ning, Yadong (Frontiers in Energy Research, 2021)
Energy issues are closely related to the development of human society and economy. Embodied energy is the total direct and indirect energy consumption required for the production of goods and services. In the context of the intensifying development of economic globalization and prosperity of international trade, embodied energy is considered as a better indicator to comprehensively reflect the nature of a country’s energy use than the direct energy use. The development of trade in value added (TiVA) accounting and global value chain theory has brought new ideas to embodied energy research. This study applies TiVA accounting to the study of embodied energy and establishes a complete framework to decompose the sources, destinations, and transfer routes of embodied energy in a country’s exports, and comprehensively depicts the embodied energy flows in China’s exports at the country and sector levels as an instance. The results show that China exports large amounts of embodied domestic energy use, and export is an important factor for the rapid growth of China’s energy and emissions. At the country level, the United States and EU28 are traditional major importers of China, and developing countries, such as Brazil, India, and Indonesia, are emerging markets. China’s embodied energy flows to different importers vary in terms of trade patterns, flow routes, and the embodied domestic energy intensities. At the sector level, the light industry and the services create more benefits, whereas manufacturing, such as chemicals and metal products, consumes more energy, and there is a mismatch between the main sectors that create economic benefits from exports and the main sectors that consume energy for exports. These results indicate that embodied energy of China’s exports has a great impact on global energy consumption and carbon emission, and the optimizing of China’s export embodied energy structure is conducive to global energy conservation and emission reduction. This article strongly suggests the importance of the global value chain decomposition framework in embodied energy research.